Património à mesa dos macaenses em Portugal - Gaspar, Marisa C. (Trabalhos de Antropologia e Etnologia, 2020)
Events of The Food and Drink Party (PCB) bring together in Lisbon several dozens of Macanese to celebrate a calendar of events, the same way as in Macao, also marked their lives in Portugal. In this context, PCB and its parties are a way of integrating, operating and maintaining the Macanese community in the host country providing to those who participate, a place of memory for the construction of a Macanese identity through feelings of longing for the traditional food they can there identify, smell and taste, and the main attraction of these meetings. This article will demonstrate how the production of PCB reunions of commensality revel an expression of communion among the various members of the community and reinforce group’s collective feeling of permanence over time. In addition, it will be analysed how the claim and maintenance for a specific Macanese culture and ethnicity has been strengthened by the political powers of Macao and China across the immaterial heritagisation of cultural items such as the Macanese gastronomy, inscribed on the list of Intangible Cultural Heritage of Macao Special Administrative Region of the People’s Republic of China (Macao SAR).